Pattern of Self-medication in Primary Dysmenorrhea among Nursing Students at a Nursing College in Eastern Nepal - Sarraf, Deependra Prasad; Karn, Basant Kumar; Singh, Smita (Nepal Journal of Health Sciences, 2022)
Introduction: Primary dysmenorrhea (PD) leads to college absenteeism, interference with daily living activities and higher intake of medications without consulting a physician and/or without a valid prescription. Objectives: To estimate the prevalence of PD, to know the pattern of self-medication in dysmenorrhea and to know the impact of dysmenorrhea on academic performance among undergraduate nursing students. Methods: A cross-sectional study was conducted among undergraduate nursing students at a nursing college in Eastern Nepal using a semi-structured questionnaire consisting of demographic characteristics, the impact of dysmenorrhea on academic performance and self-medication practices. A visual analogue scale was used to assess the severity of dysmenorrhea. Descriptive statistics were used to present the findings. Results: A total of 125 students participated in the study out of which 64 (51.20%) were 21-24 years old. Eighty-four (67.20%) students had PD that had affected academic performance negatively in 81 (96.43%) students. Fifty six (66.67%) students had a lack of concentration during study hours due to dysmenorrhea. A total of 42 (50.00%) students practiced self-medication for relieving the pain during dysmenorrhea. Mefenamic acid (90.48%) was the most commonly used analgesic. Only 29 (69.05%) students were able to mention the correct dose of the analgesic drug they take and 38 (90.48%) students were not able to mention the correct frequency of the drug intake they were taking during dysmenorrhea. Conclusions: Dysmenorrhea was highly prevalent among nursing students and had affected their academic performance negatively. The self-medication practices were not appropriate in a significant proportion of the students.